Coconut oil-based resveratrol nanoemulsion: Optimization using response surface methodology, stability assessment and pharmacokinetic evaluation. (30th September 2021) - Kotta, Sabna; Mubarak Aldawsari, Hibah; Badr-Eldin, Shaimaa M.; Alhakamy, Nabil A.; Md, Shadab
Graphical abstract: Highlights: Resveratrol proved to be beneficial in Alzheimer's disease. Nanoemulsion Optimized using Response surface methodology. Oil and surfactant concentration, and sonication intensity influenced globule size. Pharmacokinetic studies in rat proved the brain targeting efficacy. Abstract: Phytochemicals are widely studied for therapeutic applications and nanostructured delivery systems for phytochemicals are under spotlight. Resveratrol is a promising candidate for neurodegenerative disorders. In the present study, we aimed to formulate nanoemulsion of resveratrol by ultrasonication process using response surface methodology. The effect of both formulation and ultrasonication process factors were studied for the nanoemulsification process using coconut oil, Pluronic-P107, and Cremophor EL. The time, intensity, and power of ultrasonication were selected as process factors. The globule size, PDI, and zeta potential were the responses selected. The concentrations of oil and surfactant and the intensity were found to significantly influence the globule size. The concentration of resveratrol in the optimized nanoemulsion formulation was 2.6442 mg/ml. The in vitro drug release in pH 6.8 phosphate buffer as well as in vitro permeation study on goat nasal mucosa proved the superiority of the nanoemulsion formulation. On intranasal administration in the rat at a resveratrol dose of 2 mg/kg, the brain targeting efficacy of the nanoemulsion formulation was high. Overall, this research provides the benefit of intake of resveratrol containing fruits and, its incorporation into nanoemulsions system could be a promising alternative for the management of Alzheimer's disease.